POLACY WOBEC IV RZECZPOSPOLITEJ. REFLEKSJA SOCJOLOGICZNA PO WYBORACH PARLAMENTARNYCH 21 PAŹDZIERNIKA 2007 R. - Drozdowski, Rafał (Wydział Prawa i Administracji UAM, 2008)
The author looks at the result o f the recent parliamentary election in Poland to find indications o f some more general and deeper transformations that the Polish society has been lately undergoing. The paper also formulates the most likely forecasts of the direction of a further evolution of the political system in Poland and the future political situation of the winners and the losers in that latest election. The results of the election show that the pro-modernisation and pro-European attitudes are strengthening. They also confirm that Poles have rejected the model of an “educating state” or an “over-regulatory” state that aspired to administrate the reality. Further, those results seem to indicate that Poles today opt for evolutionary rather than revolutionary projects to improve the post-transformation order. What continues to be present is the crack that still divides Poland into the more liberal north-west (voting for the Civic Platform) and the more conservative south-east (consequently voting for Law and Justice). The results of the election have also revealed that the Polish society demonstrates a growing need for building social trust. Polish political scene seems to be heading towards a 3 +1 model, in which PiS (Law and Justice) will be a strong conservative right-wing party, PO (Civic Platform) a strong centrist party and LiD (Liberals and Democrats) or its successor, a strong left-wing party. PSL (Polish Peasants’ Party shall remain a party in permanent coalition with the governing ones.
POLES’ ATTITUDES TO THE IVth REPUBLIC OF POLAND SOCIOLOGICAL REFLECTION AFTER THE PARLIAMENTARY ELECTION OF 21 OCTOBER 2007